Research Progress and Development Trends of Water-Mediated Laser Machining Technology: A Review - Zhao, Qiankun (International Journal of Mechanical and Electrical Engineering, 2026)
With the ever-growing demand for miniaturized and high-precision device manufacturing in fields such as electronics, semiconductors, new energy, and medical equipment, traditional machining methods are confronted with bottlenecks like limited precision and severe thermal damage in microscale structure fabrication. Laser machining has emerged as a preferred technique for processing fine structures (e.g., micro-grooves) due to its high energy density, excellent focusing performance, and controllability. However, the thermal damage issue associated with conventional dry laser machining restricts its application expansion. Water-mediated laser machining technology effectively overcomes this limitation by leveraging the dual functions of water (cooling and slag removal), and it has evolved into three mainstream technical routes: water-guided laser machining, water-jet assisted laser machining, and underwater laser machining. This paper systematically reviews the research status and limitations of traditional laser machining, focuses on elaborating the principles, research progress, and application bottlenecks of the three water-mediated laser machining technologies, deeply analyzes the regulation mechanisms and forming laws of liquid layer parameters in underwater laser machining, and finally prospects the future development directions of this field. It aims to provide a reference for the research and engineering application of high-quality, low-damage micromachining technologies.